1986
DOI: 10.1203/00006450-198603000-00009
|View full text |Cite
|
Sign up to set email alerts
|

Role of Aldosterone for Control of Colonic NaKATPase Activity in Weanling Rats

Abstract: ABSTRACT. Ex~eriments were ~erforrned to examine MATERIALS AND METHODShow aldosterone ;noddates coloniE NaKATPase activity during the weaning period. NaKATPase activity was determined in proximal and distal colon in control rats aged 16, 20, and 40 days, in rats aged 20 and 40 days fed low sodium diet for 4 days and in 20-day-old rats adrenalectomized on day 16. In some protocols net sodium and water transport was determined with in vivo perfusion technique. In control rats colonic NaKATPase activity increased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
0

Year Published

1987
1987
1995
1995

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 20 publications
1
15
0
Order By: Relevance
“…We have also shown that, if endogenous aldosterone production is stimulated by a low salt Table I. Effect of dBcAMP administered intraarterially on the intake, the net colonic sodium absorption and NaKATPase net sodium andjluid absorption in 14-to 40-day-old rats (mean activity increase more in young than in adult rats (6).…”
Section: Discussionmentioning
confidence: 99%
“…We have also shown that, if endogenous aldosterone production is stimulated by a low salt Table I. Effect of dBcAMP administered intraarterially on the intake, the net colonic sodium absorption and NaKATPase net sodium andjluid absorption in 14-to 40-day-old rats (mean activity increase more in young than in adult rats (6).…”
Section: Discussionmentioning
confidence: 99%
“…It is well established that the circulating levels of GC and MC increase during the 3rd wk of life (3,4). To evaluate whether the temporary up-regulation of the Na,K-ATpase, H,K-ATPase, and Na-channel mRNA is due to corticoids, rats were given a single injection of betamethasone or aldosterone at 10 d of life-i.e.…”
Section: Resultsmentioning
confidence: 99%
“…These results suggest that an increased synthesis of ion transporters occurs during weaning. In the rat, the circulating level of GC and MC increases in the preweaning period (3,4), and it has been shown that the maturation of colon Na,K-ATPase activity can be accelerated by GC and MC (4, 11). To determine whether the up-regulation of the colon transporter mRNA is due to corticosteroids, betamethasone, and aldosterone were injected into 10-d-old rats-i.e.…”
Section: Control Betamethasonementioning
confidence: 99%
See 2 more Smart Citations